Qualitative data analysis - Miles, Matthew B (Sage, 2014)
Includes bibliographical references (pages 363-368) and indexes; Introduction -- Research design and management -- Ethical issues in analysis -- Fundamentals of qualitative data analysis -- Designing matrix and network displays -- Methods of exploring -- Methods of describing -- Methods of ordering -- Methods of explaining -- Methods of predicting -- Drawing and verifying conclusions -- Writing about qualitative research -- Closure; Qualitative Data Analysis: A Methods Sourcebook" is the third edition of Miles & Huberman's classic 1994 research methods text, updated and streamlined by Johnny Saldaña, author of Sage Publications' "The Coding Manual for Qualitative Researchers." Several of the data display strategies from the first and second editions of "Qualitative Data Analysis" are retained in this revision, while presenting them in re-envisioned and reorganized formats to enhance reader accessibility and comprehension